1999
DOI: 10.1152/ajpregu.1999.276.2.r591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fiber size, oxidative potential, and capillarization in human muscle by resistance exercise

Abstract: To examine the hypothesis that increases in fiber cross-sectional area mediated by high-resistance training (HRT) would result in a decrease in fiber capillarization and oxidative potential, regardless of fiber type, we studied six untrained males (maximum oxygen consumption, 45.6 ± 2.3 ml ⋅ kg−1 ⋅ min−1; mean ± SE) participating in a 12-wk program designed to produce a progressive hypertrophy of the quadriceps muscle. The training sessions, which were conducted 3 times/wk, consisted of three sets of three exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
107
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 34 publications
16
107
1
8
Order By: Relevance
“…Several studies have implicated VEGF in skeletal muscle angiogenesis regulation induce by acute aerobic or resistance exercise in both human and animals. [5][6][7][8][9][10][11] Furthermore, it has been shown that training also induce modifications of VEGF mRNA and protein expression. [12][13][14][15][16] Chronic pathological conditions, such as Chronic Obstruction Pulmonary Disease (COPD) and diabetes, 17,18 induce capillary rarefaction suggesting that VEGF is also important in the maintenance of adult skeletal muscle microvasculature.…”
Section: Angiogenesis Muscle Plasticity and Muscle Homeostasismentioning
confidence: 99%
“…Several studies have implicated VEGF in skeletal muscle angiogenesis regulation induce by acute aerobic or resistance exercise in both human and animals. [5][6][7][8][9][10][11] Furthermore, it has been shown that training also induce modifications of VEGF mRNA and protein expression. [12][13][14][15][16] Chronic pathological conditions, such as Chronic Obstruction Pulmonary Disease (COPD) and diabetes, 17,18 induce capillary rarefaction suggesting that VEGF is also important in the maintenance of adult skeletal muscle microvasculature.…”
Section: Angiogenesis Muscle Plasticity and Muscle Homeostasismentioning
confidence: 99%
“…6 Short-term high-load resistance training has been shown to evoke increases in not only muscle mass, but also in capillarity, albeit in AB subjects. [7][8][9] The significance of these adaptations is that development of cardiovascular disease and Type II diabetes with SCI may be diminished or delayed by improving the muscles and arteries of individuals with SCI. 10 One potential limitation to NMES training for individuals with SCI is excessive muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…According to other authors, strength training may increase skeletal muscle efficiency (4) and enhance skeletal muscle "metabolic stability" (50). Other studies reported, after resistance training, unchanged values of maximal O 2 uptake (V O 2 ) (6), as well as unchanged (19) or lower (42,43) mitochondrial volume density, oxidative enzyme activity, and capillary density in the hypertrophic muscles. Thus the specific effects of resistance training, with the related changes in muscle phenotype, on oxidative metabolism appear difficult to reconcile in a unifying scenario.…”
mentioning
confidence: 99%